Study and clinical evaluation of 25 cases of primary amenorrhea - Bhatu, Jaydeep J.; Bhadaraka, Govind B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Primary amenorrhea is absence of menstruation and secondary sexual characters by age of 14 years primary amenorrhea is < 1%. Development of female genital organs takes place from mullerian DUCT (paramesonephric duct). The objective of this study was to note the various causes, complete clinical picture and the management in 25 such cases of primary amenorrhea. Methods: This is a prospective study done in 25 cases. They were investigated, managed and patients were called up for follow up for their response to treatment. Results: Out of 25 cases studied, maximum cases presented at 14-16 years of age, with chief complaint of primary amenorrhea, out of which 8% were married, 44% cases were of MRKH syndrome which was the most common cause of primary amenorrhea. Conclusions: Amenorrhea has got multi factorial etiology. For patients with amenorrhea physical examination should focus on pubertal development and possible genital out flow obstruction.